Penerapan Teknologi PGPF Untuk Pengembangan Sorgum Sebagai Pangan Fungsional dan Pakan Ternak - Asniwita Asniwita; Yurleni Yurleni; Yulfita Farni; Andini Vermita Bestari (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Plant Growth Promotion Fungi (PGPF) are fungi that live in the soil near plant roots or live in plants (endophytic fungi), can increase plant growth (biofertilizer), and protect plants from plant-disturbing organisms in the form of pests and plant diseases (biopesticides). Farmers often experience obstacles due to poor plant growth due to less fertile soil and dry soil, and decreased production due to pests and plant diseases. The objectives of this community service are introducing PGPF and its benefits for plants,  exemplifying PGPF multiplication techniques and PGPF addition techniques to plants, introducing sorghum and low-cost farming with high competitiveness. To achieve these objectives, the methods applied are: (1) PGPF socialization, (2) counseling on the benefits of PGPF as a biofertilizer and biopesticide, (3) plot demonstration. The results of the activity are (1) farmers in Kota Baru Village are able to multiply and add PGPF to the soil and plants, (2) farmers are able to apply sorghum cultivation techniques as a food material in order to diversify food and availability of animal feed in every environmental condition of the dry season and rainy season. All parts of the sorghum plant (seeds, leaves, stems) can be utilized, so there is no waste (zero wasted).